A ludicidade e a criança: (des)arranjos no ensino fundamental de nove anos - Azevedo, Nair Correia Salgado de [UNESP]; Betti, Mauro [UNESP]; Lima, José MIlton de [UNESP] (My University, 2010)
The anticipation of the beginning of Elementary School for six-year-old children, recently imposed by the Brazilian federal law, brought controversies and debates about the organization of the curriculum, routines, contents and activities, spaces and objects, conduct of behavior of teachers and parents, as well as about the policies of teachers’ training, amongst other issues. The present article, supported by advances of scientific production on children formal education, considers the changes in the concepts of children education and, consequently, in curricular practices. For this purpose, games and fun are taken as object of analysis and discussion, and the playfulness is proposed as a central curricular axle in the initial years of Elementary Education.

A antecipação do início do Ensino Fundamental para as crianças de seis anos, imposta recentemente pela legislação federal brasileira, gerou polêmicas e debates sobre a organização do currículo, rotinas, conteúdos e atividades, espaços e objetos, condutas dos professores e familiares, bem como sobre as políticas de formação de professores, dentre outros temas. O presente artigo, apoiado em avanços da produção científica sobre a educação formal das crianças, considera que são necessárias mudanças nas concepções de educação para a infância, e, consequentemente, nas práticas curriculares. Para tanto, toma o jogo e a brincadeira como objeto de análise e discussão, e propõe a ludicidade como eixo curricular central nos anos iniciais do Ensino Fundamental.
The playfulness and the child: (dis)arrangements in Elementary Education of nine-year-olds
Keywords: Elementary school; Childhood; Playfulness; Ensino fundamental; Infância; Ludicidade